Highlighting the complex interrelationship between the concepts of trust and control - Beusch, Peter (Proceedings of Pragmatic Constructivism, 2012)
This paper presents the area of management control and trust in an inter-organizational setting with an attempt to offer a fresh perspective on the complex relationship between and different understandings of the two concepts of trust and control. This is done with help of two case studies in a cross-cultural setting and involving five multinational companies that were involved in two large acquisitions. Obviously, different actor groups’ cultural and educational heritage has brought with it that dissimilar opinions exist on the subject of mainly system-based versus inter-personal based trust. The paper first demonstrates that trust and control can mean different but also the same things to different people, depending very much on the logic and values applied but also depending on if the actors were motivated more intrinsically or extrinsically. Further, what impact certain control mechanisms, or the lack thereof, have on individual’s behavior is outlined. The paper also reveals that it is difficult to find the right balance between diverse types of control and trust as time went on after the acquisitions. The main reason for this is that actors with different socio-cultural heritage use different references regarding trust and control and put unlike emphasis on what should be focused on, what should be counted, and what should be accounted for. Trust and control can mean almost identical things but the cases illustrate that, from a rhetorical and convincing point of view, system trust appears to be stronger in certain settings than inter-personal trust, as it, to particular actors, provides the impression of being in control. The contrary is true in other settings, where having ‘facts and figures’ and ‘a whole bunch ‘of accounting systems and accounting techniques not automatically mean to be in control, thus leaving more room for the use and appreciation of inter-personal trust.